2019
DOI: 10.1101/868588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic profiling of Vietnamese population from large-scale genomic analysis of non-invasive prenatal testing data

Abstract: 24The under-representation of several ethnic groups in existing genetic databases and studies 25 have undermined our understanding of the genetic variations and associated traits or diseases 26 in many populations. Cost and technology limitations remain the challenges in performing large-27 scale genome sequencing projects in many developing countries, including Vietnam. As one of 28 the most rapidly adopted genetic tests, non-invasive prenatal testing (NIPT) data offers an 29 alternative untapped resource for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The use of dense genotyping arrays followed by imputation to a haplotype reference panel has enabled population-scale genome wide associations studies to become routine in characterizing the genetic architecture of complex traits and disease. An alternative technology is low-pass whole genome sequencing followed by imputation, which has successfully used for a number of problems in statistical and population genetics (Tran et al, 2020;Pasaniuc et al, 2012;Gilly et al, 2019), and which was recently shown to recapitulate comparable disease risk stratification performance using a handful of polygenic risk scores derived from imputed array data from an independent cohort (Homburger et al, 2019). We introduced the notion of effective coverage, a quantity which describes the coverage of a sequenced sample under an ideal sampling process and which is more predictive of imputation accuracy than nominal coverage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of dense genotyping arrays followed by imputation to a haplotype reference panel has enabled population-scale genome wide associations studies to become routine in characterizing the genetic architecture of complex traits and disease. An alternative technology is low-pass whole genome sequencing followed by imputation, which has successfully used for a number of problems in statistical and population genetics (Tran et al, 2020;Pasaniuc et al, 2012;Gilly et al, 2019), and which was recently shown to recapitulate comparable disease risk stratification performance using a handful of polygenic risk scores derived from imputed array data from an independent cohort (Homburger et al, 2019). We introduced the notion of effective coverage, a quantity which describes the coverage of a sequenced sample under an ideal sampling process and which is more predictive of imputation accuracy than nominal coverage.…”
Section: Discussionmentioning
confidence: 99%
“…As genome sequencing costs have decreased over the past decade, sequencing-based alternatives to genotyping arrays have been the subject of growing interest (Wetterstrand, 2019). Specifically, low-coverage shotgun whole genome sequencing followed by imputation has been utilized for a number of problems in statistical and population genetics, from providing the backbone for graphbased pangenomes in sorghum to trait mapping in human pharmacogenetics (Tran et al, 2020;Gilly et al, 2019;Rubinacci et al, 2020;Homburger et al, 2019;Wasik et al, 2019;Jensen et al, 2020;Cai et al, 2015a;Liu et al, 2018). As an intuition for why this approach is useful, a sample sequenced at a target coverage of 0.5× is expected to have at least one read on 33 million of the 85 million sites in the 1000 Genomes Phase 3 release, whereas a genotyping array will probe a number of variants which is one to two orders of magnitude fewer, albeit with higher average accuracy (Consortium et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1 in 20) of the Vietnamese population. populations, had been reported previously in [9]. Two other autosomal recessive diseases were found with relatively high carrier frequencies, including hemochromatosis type 1 (HFE, 9.4% or syndrome is a multisystem disorder characterized by many clinical features, including developmental delay, intellectual disability and facial dysmorphis.…”
Section: Carrier Frequencies Of Genetic Diseases In the Vietnamese Pomentioning
confidence: 93%
“…Gurdasani et al found that nearly 78% of the participants in genetic studies had European ancestries, whereas the two major populations, Asian and African, only accounted for 11% and 2.4%, respectively [6]. Indeed, genetic research on the Vietnamese population still lags behind other Western and Asian populations, despite recent efforts of genome sequencing projects in the country [8, 9]. There has been no research to study the prevalence of inherited disorders in the Vietnamese population.…”
Section: Introductionmentioning
confidence: 99%